2018
DOI: 10.1002/jcsm.12358
|View full text |Cite
|
Sign up to set email alerts
|

Host phenotype is associated with reduced survival independent of tumour biology in patients with colorectal liver metastases

Abstract: Background Most prognostic scoring systems for colorectal liver metastases (CRLMs) account for factors related to tumour biology. Little is known about the effects of the host phenotype to the tumour. Our objective was to delineate the relationship of systemic inflammation and body composition features [i.e. low skeletal muscle mass (sarcopenia) and low visceral adipose tissue (VAT)], two well‐described host phenotypes in cancer. Methods Clinical data and pre‐operative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…All DEXA studies [14,15,16] included in this review used LUNAR DPX-L & LUNAR PRODIGY software (Discovery ® , Hologic, Bedford, MA USA) for body composition measurements. Of the 20 CT studies, six studies [17,18,19,20,21,22] used Slice-O-Matic software (TomoVision, Montreal, Quebec, Canada), three studies [23,24,25] used Image J software (NIH Image J version 1.47, ), two studies [26,27] used Synapse Vincent software (Fujifilm Medical, Tokyo, Japan), two studies [28,29] used Infinitt PACS software (INFINITT Healthcare Co., Ltd, Seoul, Korea) , one study [30] used OSIRIX software (OSIRIX ®, Version 3.3, downloaded from ), one study [31] used Terrarecon software (Terarecon 3.4.2.11, San Mateo, CA, USA), one study [32] used Somatom Software (Somatom Sensation, Siemens, Fairfield, CT, USA) and manual CT images analyses was performed in four studies [33,34,35,36]. All the 20 CT studies used same thresholds for muscle (−29 to 150 HU) to measure SMA, which were normalized for height 2 to define SMI.…”
Section: Resultsmentioning
confidence: 99%
“…All DEXA studies [14,15,16] included in this review used LUNAR DPX-L & LUNAR PRODIGY software (Discovery ® , Hologic, Bedford, MA USA) for body composition measurements. Of the 20 CT studies, six studies [17,18,19,20,21,22] used Slice-O-Matic software (TomoVision, Montreal, Quebec, Canada), three studies [23,24,25] used Image J software (NIH Image J version 1.47, ), two studies [26,27] used Synapse Vincent software (Fujifilm Medical, Tokyo, Japan), two studies [28,29] used Infinitt PACS software (INFINITT Healthcare Co., Ltd, Seoul, Korea) , one study [30] used OSIRIX software (OSIRIX ®, Version 3.3, downloaded from ), one study [31] used Terrarecon software (Terarecon 3.4.2.11, San Mateo, CA, USA), one study [32] used Somatom Software (Somatom Sensation, Siemens, Fairfield, CT, USA) and manual CT images analyses was performed in four studies [33,34,35,36]. All the 20 CT studies used same thresholds for muscle (−29 to 150 HU) to measure SMA, which were normalized for height 2 to define SMI.…”
Section: Resultsmentioning
confidence: 99%
“…The assessment of longitudinal changes of body composition by computed tomography (CT) revealed three phenotypes of body wasting in these patients: patients who lost skeletal muscle and fat tissue, patients who only lost fat tissue, and patients without wasting who had a significantly improved survival. Several other studies investigated patients with different types of gastrointestinal cancer and reported either a loss of muscle tissue or a loss of both skeletal muscle and adipose tissue mass . In addition, loss of cardiac muscle tissue in cancer cachexia (CC) has been shown in clinical and experimental studies …”
mentioning
confidence: 99%
“…The low muscle mass detected by CT images can occur in the absence of systemic inflammation in other malignancies, such as colorectal cancer, but the proportion of patients with low-muscularity is substantially greater in the presence of systemic inflammation [49]. In cases where the inflammation coexists with low muscle mass, the prognosis is especially poor [50]. Taken together, we identified a specific set of upregulated genes coding for secreted proteins that may constitute potential mediators of muscle loss in NSCLC.…”
Section: Discussionmentioning
confidence: 99%